Analisis Perkembangan Riset Akuntansi Keperilakuan Studi Pada Jurnal Behavioral Research In Accounting (1998-2003) - Tan Ming Kuang; Se Tin (Jurnal Akuntansi)
This research aims to analyze growth direction of research in journal of BRIA period 1998-2003. Growth analysis is done at topic / article content, research method, and research subject used by writer of article of BRIA 1998-2003. Topic /article content is classified using taxonomy of Birnberg and Shield (1989) which have been modified by Meyer and Rigsby (2001). Technics of descriptive analysis were used to analyze data.